Water-resistant super-strong corundum paste ceramic tile back adhesive and preparation method thereof

By using components such as gold steel sand particles and superhydrophobic surface treatment agents in the ceramic tile back glue, a high viscosity and dense structure is formed, which solves the problem of insufficient water resistance and bonding strength of the ceramic tile back glue in the existing technology, and achieves moisture in the process Improved stability and deformation resistance in the environment are suitable for the adhesion of large ceramic tiles.

CN119307197APending Publication Date: 2025-01-14FOSHAN YONGLAN BUILDING MATERIALS COATING TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411419896.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing ceramic tile backing has shortcomings in water resistance and bonding strength, especially in humid environments, which can easily cause the tiles to fall off and crack, making it difficult to meet the adhesion requirements of large or heavy tiles, and have limited resistance to deformation.

Method used

Using a water-resistant super strong gold steel sand-shaped ceramic tile backing glue, including gold steel sand particles, fillers, superhydrophobic surface treatment agents, aqueous resins, dispersants, thickeners and curing agents, it is processed through specific ratios and processes. The adhesive backing with high viscosity and dense structure is formed to improve its water resistance and bond strength.

Benefits of technology

It significantly improves the water resistance and bonding strength of the tiles' adhesive backing, extends the service life of the tiles, enhances the resistance to deformation, and has environmentally friendly performance, suitable for humid environments and the adhesion of large tiles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005080457870000071
    Figure BDA0005080457870000071
  • Figure BDA0005080457870000081
    Figure BDA0005080457870000081
  • Figure BDA0005080457870000091
    Figure BDA0005080457870000091
Patent Text Reader

Abstract

The invention provides a waterproof super-strong corundum pasty ceramic tile back adhesive and a preparation method thereof. The back adhesive is prepared from corundum particles, filler, a super-hydrophobic surface treating agent, water-based resin, a dispersing agent, a thickening agent and a curing agent according to a specific proportion. Wherein the particle size of emery particles is 0.1-1.0 mm, and the curing agent is benzophenone and benzoin dimethyl ether in a specific mass ratio. The super-hydrophobic surface treating agent is prepared by adding an organic silicon emulsion and the like into a polymer emulsion for pre-emulsification, and then adding an initiator and dodecafluoroheptyl methacrylate for reaction. The preparation method comprises the steps of premixing, additive mixing, high-speed dispersion, vacuum curing and the like. The ceramic tile back adhesive has excellent water resistance and deformation resistance, can effectively improve the bonding strength of a ceramic tile and a base layer, can keep stable performance in a humid environment, prolongs the service life, and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of tile adhesive, and in particular to a water-resistant super-strong corundum paste-like tile adhesive and a preparation method thereof. Background Art

[0002] With the continuous development of the building decoration industry, ceramic tiles are widely used as a common decorative material in the decoration of indoor and outdoor walls and floors. At the same time, the performance requirements for ceramic tile adhesives are increasing. However, the pasting quality of ceramic tiles has always been one of the focal issues of people's attention. Traditional ceramic tile pasting methods usually use materials such as cement mortar, but these materials have certain limitations in terms of water resistance and bonding strength.

[0003] The existing tile adhesives do not perform well in terms of water resistance. When encountering water erosion, it is easy to cause the bonding strength to decrease, and the tiles will become hollow and fall off. Especially in humid environments such as kitchens and bathrooms, this problem is more prominent; traditional tile adhesives often cannot meet the requirements for pasting large tiles or heavy tiles, and the bonding strength is not high enough, which can easily cause the tiles to loosen and shift during use; in the case of temperature changes, deformation of the base layer, etc., the existing tile adhesives have limited anti-deformation ability and cannot adapt well to different use environments, which can easily cause the tiles to crack and break. In addition, with the continuous increase in tile specifications and the improvement in quality, the requirements for pasting materials are also getting higher and higher. Therefore, the development of a super-water-resistant tile adhesive has become an urgent need in the current field of architectural decoration. Summary of the invention

[0004] In view of this, the present invention proposes a water-resistant super-strong diamond abrasive paste-like tile adhesive and a preparation method thereof to solve the above problems.

[0005] The technical solution of the present invention is achieved as follows: a water-resistant super-strong corundum paste-like tile adhesive comprises the following raw materials in parts by weight: 30-40 parts of corundum particles, 10-30 parts of fillers, 3-8 parts of super-hydrophobic surface treatment agents, 10-18 parts of water-based resins, 1-5 parts of dispersants, 2-8 parts of thickeners, and 3-6 parts of curing agents; the particle size of the corundum particles is 0.1-1.0 mm, and the curing agent is diphenyl ethyl ketone and dimethyl benzoate in a mass ratio of (8-12): (2-6).

[0006] Furthermore, a water-resistant super-strong diamond sand paste-like tile adhesive comprises the following raw materials in parts by weight: 35 parts of diamond sand particles, 20 parts of filler, 5 parts of super-hydrophobic surface treatment agent, 15 parts of water-based resin, 3 parts of dispersant, 5 parts of thickener, and 4 parts of curing agent.

[0007] Furthermore, a water-resistant super-strong diamond sand paste-like tile adhesive, the water-based resin is selected from one or more of acrylic resin, polyurethane resin, and epoxy resin.

[0008] Furthermore, the filler is one or a combination of quartz powder, talcum powder, and calcium carbonate, which is ground to 5-30 μm.

[0009] Furthermore, the super hydrophobic surface treatment agent is pre-emulsified by adding silicone emulsion, emulsifier and deionized water to the polymer emulsion, the volume ratio of the polymer emulsion, silicone emulsion, emulsifier and deionized water is 10: (0.5-2): (0.1-0.5): (10-30), stirring for 15-60 minutes at a temperature of 30-60° C. and a stirring speed of 1000-3000 rpm to form a uniform pre-emulsion, and then adding an initiator and an emulsifier to the pre-emulsion, raising the temperature to 60-90° C., stirring for 10-20 minutes, and then adding dodecafluoroheptyl methacrylate in an amount of 1-20% of the mass of the polymer emulsion, continuing the reaction for 30-50 minutes, and cooling to room temperature after completion to obtain a hydrophobic surface treatment agent.

[0010] Furthermore, the polymer emulsion is one or a combination of styrene-acrylic emulsion, pure acrylic emulsion or silicone-acrylic emulsion.

[0011] Furthermore, the emulsifier is any one of octylphenol polyoxyethylene ether, sodium dodecylbenzene sulfonate, sodium dodecyl diphenyl ether disulfonate, and hexadecyl trimethyl ammonium chloride.

[0012] Furthermore, the dispersant is a polycarboxylic acid sodium salt, sodium alkylbenzene sulfonate, and nonylphenol polyoxyethylene ether in a mass ratio of (5.8-9.2):(3.2-5.5):(1.2-3.5). It can be adsorbed on the surface of corundum particles and generate electrostatic repulsion to disperse them, avoiding sedimentation and coarsening.

[0013] Furthermore, the thickener is hydroxyethyl cellulose or hydroxypropyl methyl cellulose.

[0014] Furthermore, a method for preparing a water-resistant super-strong diamond sand paste-like tile adhesive comprises the following steps:

[0015] S1. Premixing: Add corundum and filler into the disperser and disperse at 50-100 rpm for 20-40 minutes until uniformly dispersed;

[0016] S2, additive mixing: the water-based resin, dispersant, thickener and super hydrophobic surface treatment agent are mixed, first at a low speed of 100-200 rpm to mix evenly, then at a medium speed of 300-500 rpm to refine and disperse, stirring time 15-20min, to form a uniform emulsion system;

[0017] S3, high-speed dispersion: slowly add the pre-mixed corundum particles and fillers into the above emulsion, and start the high-speed disperser for dispersion at a stirring speed of 1500-3000rpm, a stirring time of 30-60min, and adjust the viscosity to 5000-20000mPa·s;

[0018] S4. Vacuum curing: While stirring, slowly continue to add curing agent, continue stirring at 30-50℃ for 10-30min, place in a vacuum pump, evacuate to -0.08~-0.1MPa, maintain for 20-40min, release air, return to normal pressure, and obtain water-resistant super strong corundum paste-like tile adhesive.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] (1) Excellent water resistance: By introducing a special super-hydrophobic surface treatment agent, an effective waterproof barrier is formed on the adhesive surface, which greatly improves the stability of the tile adhesive in a humid environment. Even under long-term immersion or high humidity conditions, it can effectively prevent moisture penetration, maintain bonding strength, and prevent tiles from falling off, thereby extending the service life of the tiles.

[0021] (2) Enhanced bonding strength and durability: Synergistic bonding of multiple ingredients: Water-based resin, filler, dispersant, thickener and other ingredients interact with each other to improve the bonding performance of the adhesive. Water-based resin can form chemical bonds with the surface of tiles and the base layer to enhance the bonding force; fillers can fill gaps and improve the density of the adhesive; dispersants and thickeners can ensure that all ingredients are evenly dispersed, improving the stability and bonding performance of the adhesive. The addition of corundum particles not only improves the mechanical strength of the adhesive, but also increases the friction between the tiles and the substrate, enhancing the bonding effect. At the same time, the optimized curing agent system ensures that the adhesive forms a dense cross-linked network during the curing process, further improving the durability and anti-aging performance of the adhesive.

[0022] (3) Outstanding environmental performance: As one of the main components of adhesive, water-based resin is environmentally friendly and non-toxic. Compared with traditional organic solvent-based resin, water-based resin does not contain harmful volatile organic compounds and is harmless to the environment and human health; fillers, dispersants, thickeners and other ingredients are mostly made of environmentally friendly materials and meet environmental protection requirements. During the preparation and use process, no substances harmful to the environment are produced. It is a green and environmentally friendly tile adhesive product. DETAILED DESCRIPTION

[0023] In order to better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention.

[0024] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.

[0025] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.

[0026] Example 1

[0027] A water-resistant super-strong diamond sand paste-like tile adhesive: comprising the following raw materials by weight: 30 parts of diamond sand particles, 10 parts of fillers, 3 parts of super-hydrophobic surface treatment agents, 10 parts of water-based resins, 1 part of dispersants, 2 parts of thickeners, and 3 parts of curing agents;

[0028] The particle size of the diamond sand particles is 0.1 mm;

[0029] The filler is quartz powder, ground to 5 μm;

[0030] The water-based resin is selected from acrylic resin;

[0031] The super hydrophobic surface treatment agent is prepared by adding silicone emulsion, emulsifier and deionized water to a polymer emulsion for pre-emulsification, wherein the volume ratio of the polymer emulsion, silicone emulsion, emulsifier and deionized water is 10:0.5:0.1:10, stirring for 15 minutes at a temperature of 30°C and a stirring speed of 1000 rpm to form a uniform pre-emulsion, then adding an initiator and an emulsifier to the pre-emulsion, raising the temperature to 60°C, stirring for 10 minutes, and then adding dodecafluoroheptyl methacrylate in an amount of 1% of the mass of the polymer emulsion, continuing the reaction for 30 minutes, and cooling to room temperature after the reaction to obtain a hydrophobic surface treatment agent; the polymer emulsion is a styrene-acrylic emulsion; and the emulsifier is octylphenol polyoxyethylene ether;

[0032] The dispersant is a sodium salt of polycarboxylate, sodium alkylbenzene sulfonate, and nonylphenol polyoxyethylene ether in a mass ratio of 5.8:3.2:1.2;

[0033] The thickener is hydroxyethyl cellulose.

[0034] Example 2

[0035] A water-resistant super-strong diamond sand paste-like tile adhesive: comprising the following raw materials by weight: 40 parts of diamond sand particles, 30 parts of filler, 8 parts of super-hydrophobic surface treatment agent, 18 parts of water-based resin, 5 parts of dispersant, 8 parts of thickener, and 6 parts of curing agent;

[0036] The particle size of the diamond sand particles is 1.0 mm;

[0037] The filler is talcum powder and calcium carbonate in a mass ratio of 1:1, ground to 30 μm;

[0038] The water-based resin is selected from polyurethane resin;

[0039] The super hydrophobic surface treatment agent is prepared by adding silicone emulsion, emulsifier and deionized water to a polymer emulsion for pre-emulsification, wherein the volume ratio of the polymer emulsion, silicone emulsion, emulsifier and deionized water is 10:2:0.5:30, stirring for 60 minutes at a temperature of 60°C and a stirring speed of 3000 rpm to form a uniform pre-emulsion, and then adding an initiator and an emulsifier to the pre-emulsion, raising the temperature to 90°C, stirring for 20 minutes, and then adding dodecafluoroheptyl methacrylate in an amount of 20% of the mass of the polymer emulsion, continuing the reaction for 50 minutes, and cooling to room temperature after the reaction to obtain a hydrophobic surface treatment agent; the polymer emulsion is; the emulsifier is sodium dodecyl diphenyl ether disulfonate;

[0040] The dispersant is sodium polycarboxylate, sodium alkylbenzene sulfonate, and nonylphenol polyoxyethylene ether in a mass ratio of 9.2:5.5:3.5;

[0041] The thickener is hydroxypropyl methylcellulose.

[0042] Example 3

[0043] A water-resistant super-strong diamond sand paste-like tile adhesive: comprising the following raw materials by weight: 35 parts of diamond sand particles, 20 parts of filler, 5 parts of super-hydrophobic surface treatment agent, 15 parts of water-based resin, 3 parts of dispersant, 5 parts of thickener, and 4 parts of curing agent;

[0044] The particle size of the diamond sand particles is 0.5 mm;

[0045] The filler is quartz powder, talcum powder and calcium carbonate in a mass ratio of 1:1:1, ground to 20 μm;

[0046] The water-based resin is selected from epoxy resin;

[0047] The super hydrophobic surface treatment agent is prepared by adding silicone emulsion, emulsifier and deionized water to a polymer emulsion for pre-emulsification, wherein the volume ratio of the polymer emulsion, silicone emulsion, emulsifier and deionized water is 10:1.2:0.3:20, stirring for 35 minutes at a temperature of 45°C and a stirring speed of 2000rpm to form a uniform pre-emulsion, and then adding an initiator and an emulsifier to the pre-emulsion, raising the temperature to 70°C, stirring for 15 minutes, and then adding dodecafluoroheptyl methacrylate in an amount of 15% of the mass of the polymer emulsion, continuing the reaction for 40 minutes, and cooling to room temperature after the reaction to obtain a hydrophobic surface treatment agent; the polymer emulsion is a silicone-acrylic emulsion; the emulsifier is hexadecyltrimethylammonium chloride;

[0048] The dispersant is a sodium salt of polycarboxylate, sodium alkylbenzene sulfonate, and nonylphenol polyoxyethylene ether in a mass ratio of 7.5:4.2:2.5;

[0049] The thickener is hydroxyethyl cellulose:

[0050] The above examples 1-3 adopt the following preparation method:

[0051] S1. Premixing: Add corundum and filler into a disperser and disperse at 80 rpm for 30 min until uniformly dispersed;

[0052] S2, additive mixing: the water-based resin, dispersant, thickener and super-hydrophobic surface treatment agent are mixed, firstly mixed at a low speed of 150 rpm, then finely dispersed at a medium speed of 400 rpm, and the stirring time is 18 minutes to form a uniform emulsion system;

[0053] S3, high-speed dispersion: slowly add the pre-mixed corundum particles and fillers into the above emulsion, and start the high-speed disperser for dispersion at a stirring speed of 2000 rpm for 50 min, and adjust the viscosity to 10000 mPa·s;

[0054] S4. Vacuum curing: While stirring, slowly continue to add curing agent, continue stirring at 40°C for 20 minutes, place in a vacuum pump, evacuate to -0.09MPa, maintain for 30 minutes, release air, return to normal pressure, and obtain water-resistant super-strong corundum paste-like tile adhesive.

[0055] Comparative Example 1

[0056] The difference between this comparative example and Example 3 is that the water-resistant super-strong diamond sand paste-like tile adhesive comprises the following raw materials in parts by weight: 20 parts of diamond sand particles, 33 parts of fillers, 2 parts of super-hydrophobic surface treatment agents, 5 parts of water-based resins, 6 parts of dispersants, 10 parts of thickeners, and 1 part of curing agents.

[0057] Comparative Example 2

[0058] The difference between this comparative example and Example 3 is that the raw materials of the water-resistant super-strong corundum paste-like tile adhesive do not contain a super-hydrophobic surface treatment agent.

[0059] Comparative Example 3

[0060] The difference between this comparative example and Example 3 is that the raw materials of the water-resistant super-strong corundum paste-like tile adhesive do not contain a curing agent.

[0061] Comparative Example 4

[0062] The difference between this comparative example and Example 3 is that the super hydrophobic surface treatment agent in the raw material of the water-resistant super strong corundum paste-like tile backing adhesive is styrene acrylic emulsion.

[0063] Test Example 1-Water resistance test

[0064] 1. Specimen preparation

[0065] 1. Prepare materials:

[0066] Tiles: Choose tiles that meet relevant standards and ensure that the tile surface is clean, flat, free of cracks and defects.

[0067] Adhesive: Emery paste-like tile adhesive prepared in Examples 1-3 and Comparative Examples 1-4.

[0068] Base material: cement mortar board, concrete board, as the base for ceramic tiles. The base material should have a certain strength and flatness and meet the requirements of relevant standards.

[0069] 2. Apply the adhesive: Apply the adhesive evenly on the back of the tile. The thickness should meet the requirements of the product manual, which is 2mm. Use a scraper or brush to apply the adhesive, ensuring that the adhesive covers the entire back of the tile and the thickness is uniform.

[0070] 3. Paste the tiles: Paste the tiles with adhesive on the base material. Follow the standard pasting method and apply appropriate pressure to ensure that the tiles fit tightly to the base. You can use a rubber hammer to gently tap the tiles to make them better bond with the base.

[0071] 4. Curing of test pieces: Curing the pasted test pieces at a temperature of 23℃±2℃ and a relative humidity of 50%±5% for 14 days.

[0072] 2. Water immersion test

[0073] 1. Soak the specimens: Place the above-cured specimens in a container filled with clean water, with the water level higher than the surface of the specimens and the water temperature at 23℃±2℃, and soak for 72 hours.

[0074] 2. Observation and testing: During the immersion process, regularly observe the changes in the appearance of the test piece to check for bulging, falling off, cracking, etc. At the same time, you can use a tool to gently tap the test piece and listen to the sound to determine whether there is a hollowing phenomenon.

[0075] After the prescribed soaking time is over, take out the specimen, wipe off the surface moisture, and conduct a bond strength test. The tensile bond strength test method can be used, referring to the "Ceramic Wall and Floor Tile Adhesive" JC / T547-2017 test standard. The test results should be compared with the bond strength before soaking to evaluate the water resistance of the adhesive.

[0076] 3. Test Results

[0077]

[0078]

[0079] The water resistance test results show that the prepared corundum paste-like tile adhesive (Examples 1-3) can still maintain good bonding performance and stability after long-term immersion, without obvious shedding or cracking, and has high water resistance. In contrast, the comparative samples showed varying degrees of deficiencies in bonding strength changes and shedding / cracking.

[0080] Compared with Comparative Example 1, Example 3 pays more attention to the balance and synergy between the components in the formula design. The content of diamond sand particles is 35 parts, which is significantly increased compared with 20 parts of Comparative Example 1. The ratio of the reinforcing phase in the adhesive is significantly increased, which helps to form a more solid bonding interface and improve the overall bonding strength. At the same time, the content of the super-hydrophobic surface treatment agent is increased from 2 parts of Comparative Example 1 to 5 parts. This surface treatment agent can effectively reduce the infiltration and erosion of water molecules on the bonding interface, thereby significantly improving the water resistance of the adhesive. After long-term immersion, the adhesive of Example 3 can maintain a higher bonding strength and reduce the performance degradation caused by water erosion.

[0081] Embodiment 3 is compared with comparative examples 2 and 4. Super hydrophobic surface treatment agent is added in embodiment 3. Compositions such as silicone emulsion and dodecafluoroheptyl methacrylate have extremely low surface energy. When super hydrophobic surface treatment agent is applied to tile adhesive, these low surface energy components will form a dense film on the adhesive surface. This film can greatly reduce the surface energy of adhesive, making it difficult for moisture to adhere and penetrate on its surface, forming a protective layer on the adhesive surface, effectively blocking the penetration and erosion of water molecules. This characteristic enables the adhesive prepared by embodiment 3 to still maintain high bonding strength and stability under humid conditions. In the process of preparing super hydrophobic surface treatment agent, micro-nano structure will be formed on the adhesive surface by steps such as pre-emulsification and reaction. This micro-nano structure further enhances the super hydrophobic performance of adhesive. Tiny protrusions and depressions can make water droplets form spherical on the surface, reduce the contact area with adhesive, thereby improving the water resistance of adhesive. In contrast, Comparative Example 2, due to not containing a super-hydrophobic surface treatment agent, has a significantly decreased water resistance, and is prone to problems such as decreased bonding strength, falling off or cracking after long-term immersion. In Comparative Example 4, since the super-hydrophobic surface treatment agent is replaced by styrene-acrylic emulsion, the adhesive surface loses super-hydrophobicity, causing a significant decrease in water resistance. Although styrene-acrylic emulsion has certain waterproof properties, it cannot be compared with the super-hydrophobic surface treatment agent, and cannot effectively block the long-term penetration of water molecules.

[0082] The super-hydrophobic surface treatment agent not only improves the water resistance of the adhesive surface, but also enhances the protective ability of the interface between the adhesive and the tile. In a humid environment, the super-hydrophobic surface can reduce the intrusion of moisture and other harmful substances and protect the bonding interface from damage. In comparative example 4, due to the lack of a super-hydrophobic surface treatment agent, the interface between the adhesive and the tile is more susceptible to erosion by moisture and other harmful substances, resulting in a decrease in bonding performance and even possible peeling or shedding.

[0083] Compared with Comparative Example 3, Example 3 adds the curing agent of the present invention. The curing agent promotes the cross-linking reaction of components such as resin to form a tight three-dimensional network structure, which can effectively block the penetration and erosion of water molecules. Therefore, the adhesive prepared in Example 3 can still maintain high bonding strength and stability when immersed for a long time or in a high humidity environment. In contrast, since Comparative Example 3 does not contain a curing agent, its internal structure may be relatively loose and cannot effectively block the intrusion of moisture, resulting in a significant decrease in water resistance. The curing agent not only enhances the strength of the adhesive itself, but also improves the interface stability between the adhesive and the tile. In a humid environment, the interface is prone to become an intrusion channel for moisture and other harmful substances. The curing agent in Example 3 reduces the defects and gaps at the interface by promoting tight bonding between the adhesive and the tile, thereby improving the water resistance of the interface.

[0084] Test Example 2-Deformation Resistance Test

[0085] According to the specimen preparation method of Test Example 1, a universal testing machine was used to apply a pressure of 100 N to the above-mentioned ceramic tile, and the pressure was gradually increased to 500 N at a rate of 10 N / min, simulating the external force that the ceramic tile may be subjected to in actual use.

[0086] Test results:

[0087]

[0088]

[0089] The above results show that under different pressures, the deformation increases relatively steadily. In the process of pressure change from 100N to 500N, it shows that the diamond paste-like tile adhesive can better control the deformation of the tile within a certain pressure range. This shows that the adhesive product of the embodiment group has a strong anti-deformation ability and can adapt to a certain degree of external force to maintain the stability of the tile.

[0090] Compared with Comparative Example 3, Example 3 contains a curing agent. During the preparation process, the curing agent reacts with other components to form a stable three-dimensional network structure. This structure can effectively enhance the mechanical strength of the tile adhesive and improve its ability to resist deformation due to external forces. When the tile is subjected to external pressure, the adhesive of Example 3 can better disperse and withstand the pressure, thereby reducing the deformation of the tile. The presence of the curing agent helps to increase the bonding strength between the adhesive and the tile and the base layer. This tight bonding enables the tile and the adhesive to form a whole and jointly resist the action of external forces. When subjected to deformation force, the adhesive of Example 3 can better transfer the force to the base layer and reduce the local deformation of the tile.

[0091] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A water-resistant super-strong diamond sand paste-like tile adhesive, characterized by: The invention comprises the following raw materials in parts by weight: 30-40 parts of corundum particles, 10-30 parts of fillers, 3-8 parts of super-hydrophobic surface treatment agents, 10-18 parts of water-based resins, 1-5 parts of dispersants, 2-8 parts of thickeners, and 3-6 parts of curing agents; the particle size of the corundum particles is 0.1-1.0 mm, and the curing agent is benzoin and dimethyl ether in a mass ratio of (8-12):(2-6).

2. The water-resistant super-strong diamond abrasive paste-like tile adhesive as claimed in claim 1, characterized in that: The invention comprises the following raw materials in parts by weight: 35 parts of diamond sand particles, 20 parts of fillers, 5 parts of super hydrophobic surface treatment agents, 15 parts of water-based resins, 3 parts of dispersants, 5 parts of thickeners and 4 parts of curing agents.

3. The water-resistant super-strong diamond abrasive paste-like tile adhesive as claimed in claim 1, characterized in that: The water-based resin is selected from one or more of acrylic resin, polyurethane resin and epoxy resin.

4. The water-resistant super-strong diamond abrasive paste-like tile adhesive as claimed in claim 1, characterized in that: The filler is one or a combination of quartz powder, talcum powder, and calcium carbonate, which is ground to 5-30 μm.

5. The water-resistant super-strong diamond abrasive paste-like tile adhesive as claimed in claim 1, characterized in that: The super hydrophobic surface treatment agent is prepared by adding an organosilicon emulsion, an emulsifier and deionized water to a polymer emulsion for pre-emulsification, wherein the volume ratio of the polymer emulsion, the organosilicon emulsion, the emulsifier and the deionized water is 10:(0.5-2):(0.1-0.5):(10-30), stirring for 15-60 minutes at a temperature of 30-60° C. and a stirring speed of 1000-3000 rpm to form a uniform pre-emulsified liquid, then adding an initiator and an emulsifier to the pre-emulsified liquid, raising the temperature to 60-90° C., stirring for 10-20 minutes, and then adding dodecafluoroheptyl methacrylate in an amount of 1-20% of the mass of the polymer emulsion, continuing the reaction for 30-50 minutes, and cooling to room temperature after the reaction is completed to obtain the hydrophobic surface treatment agent.

6. The water-resistant super-strong diamond abrasive paste-like tile adhesive as claimed in claim 5, characterized in that: The polymer emulsion is one of styrene acrylic emulsion, pure acrylic emulsion or silicone acrylic emulsion or a combination of several of them.

7. The water-resistant super-strong diamond abrasive paste-like tile adhesive as claimed in claim 5, characterized in that: The emulsifier is any one of octylphenol polyoxyethylene ether, sodium dodecylbenzene sulfonate, sodium dodecyl diphenyl ether disulfonate, and hexadecyl trimethyl ammonium chloride.

8. The water-resistant super-strong diamond abrasive paste-like tile adhesive as claimed in claim 1, characterized in that: The dispersant is a sodium salt of polycarboxylate, sodium alkylbenzene sulfonate and nonylphenol polyoxyethylene ether in a mass ratio of (5.8-9.2):(3.2-5.5):(1.2-3.5).

9. The water-resistant super-strong diamond abrasive paste-like tile adhesive as claimed in claim 1, characterized in that: The thickener is hydroxyethyl cellulose or hydroxypropyl methyl cellulose.

10. The method for preparing a water-resistant super-strong diamond abrasive paste-like tile adhesive as claimed in claim 1, characterized in that: The following steps are involved: S1. Premixing: Add corundum and filler into the disperser and disperse at 50-100 rpm for 20-40 minutes until uniformly dispersed; S2, additive mixing: the water-based resin, dispersant, thickener and super hydrophobic surface treatment agent are mixed, first at a low speed of 100-200 rpm to mix evenly, then at a medium speed of 300-500 rpm to refine and disperse, stirring time 15-20min, to form a uniform emulsion system; S3, high-speed dispersion: slowly add the pre-mixed corundum particles and fillers into the above emulsion, and start the high-speed disperser for dispersion at a stirring speed of 1500-3000rpm, a stirring time of 30-60min, and adjust the viscosity to 5000-20000mPa·s; S4. Vacuum curing: While stirring, slowly continue to add curing agent, continue stirring at 30-50℃ for 10-30min, place in a vacuum pump, evacuate to -0.08~-0.1MPa, maintain for 20-40min, release air, return to normal pressure, and obtain water-resistant super strong corundum paste-like tile adhesive.